Familial juvenile polyposis coli; increased risk of colorectal cancer. - Järvinen, H (1984)
Six patients from one family and one solitary patient with juvenile polyposis coli are described. The histological changes in colonic polyps formed a spectrum from juvenile polyps, through focal to extensive adenomatous change, to adenocarcinomas. One patient aged 49 years had an adenocarcinoma of the colon and in another, aged 33, with rectal polyps and metastatic cancer this was suspected although the primary tumour was not located. Two additional patients, aged 19 and 41 years, had severe adenomatous dysplasia in a juvenile polyp. Four patients also had gastroduodenal polyps. The present findings clearly contradict the previous view that juvenile polyposis coli is not premalignant and only rarely needs surgical treatment. As other recent reports also describe frequent occurrence of neoplastic changes in juvenile polyps, colectomy, and ileorectostomy at the age of about 20 years is recommended as the treatment of choice for juvenile polyposis coli, as in patients with familial adenomatosis coli. Follow up should ideally include gastroduodenoscopy and inspection of the rectal remnant at regular intervals.